1996
DOI: 10.1172/jci118433
|View full text |Cite
|
Sign up to set email alerts
|

Human endometrial matrix metalloproteinase-2, a putative menstrual proteinase. Hormonal regulation in cultured stromal cells and messenger RNA expression during the menstrual cycle.

Abstract: Proteinases are likely effectors of endometrial menstrual breakdown. We have investigated proteinase production by human endometrial stromal cells subjected in vitro to progesterone (P) withdrawal, the physiologic stimulus for menstruation. Culture media of cells exposed to estradiol, P, or estradiol plus P had low levels of proteolytic activity similar to cultures maintained in the absence of steroids. P withdrawal, or addition of RU486 to P-treated cultures, stimulated proteinase secretion. The stromal cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0
2

Year Published

1996
1996
2011
2011

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(57 citation statements)
references
References 45 publications
4
51
0
2
Order By: Relevance
“…MMPs are important group of zinc enzymes that are responsible for degradation of extracellular matrix components such as collagen and proteoglycans in normal embryogenesis and in many disease processes such as arthritis and invasion by carcinoma (Iurlaro et al, 1999;Sillem et al, 1999). In the endometrium, it has been reported that some MMPs play important roles in endometrial physiologic characteristics and these roles are regulated by ovarian steroid hormones (Irwin et al, 1996). Mizumoto et al (2002) reported that the expression of MMP-1, -7 and -9 was enhanced in Ishikawa cells with ERa positive in the E2-containing condition according to the acceleration of their invasiveness.…”
Section: Discussionmentioning
confidence: 99%
“…MMPs are important group of zinc enzymes that are responsible for degradation of extracellular matrix components such as collagen and proteoglycans in normal embryogenesis and in many disease processes such as arthritis and invasion by carcinoma (Iurlaro et al, 1999;Sillem et al, 1999). In the endometrium, it has been reported that some MMPs play important roles in endometrial physiologic characteristics and these roles are regulated by ovarian steroid hormones (Irwin et al, 1996). Mizumoto et al (2002) reported that the expression of MMP-1, -7 and -9 was enhanced in Ishikawa cells with ERa positive in the E2-containing condition according to the acceleration of their invasiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Progesterone inhibits endometrial metalloproteinase expression, an action mediated by transforming growth factor- (Brunnel et al, 1995). As a result of progesterone withdrawal, metalloproteinase secretion and activation are increased, followed by dissolution of the extracellular matrix (Irwin et al, 1996). The enzymatic degradation of endometrium extends to the deepest extent of functional layer, where the rupture of basal arterioles contribute to bleeding that caused by the dissolution of the surface membrane.…”
Section: Mechanism Of Normal Menstruationmentioning
confidence: 99%
“…In this issue of The Journal, Irwin et al (1) report that a specific member of the matrix metalloproteinase enzyme family may be a likely effector of endometrial menstrual breakdown. The authors cultured human endometrial stromal cells in the presence of progesterone and found an augmentation of proteinase production after withdrawal of progesterone; the same results were achieved by the addition of RU486.…”
Section: Editorialmentioning
confidence: 99%
“…MMP-2 or gelatinase A, the enzyme elaborated by the endometrial stroma in the study of Irwin et al (1), is a member of the second subgroup of MMPs. This group is characterized by the existence of a fibronectin-like gelatin-binding domain adjacent to the catalytic domain (2).…”
Section: Editorialmentioning
confidence: 99%